Photocatalytic Decolorization of Industrial Wastewater Under Natural Weathering Conditions - N. Alkhateeb, Ahmed; H. Hussein, Falah; A. Asker, Kahtan (Asian Journal of Chemistry, 2016)
Industrial wastewater released from the Spinning and Textile Factory is Sanaa was photodecolorized by using a suspension of titanium dioxide or zinc oxide, as a catalyst, under natural weathering conditions. The photocatalytic decolorization of the dyes was studied under different conditions, such as type of catalyst and the pH. The decolorization rates of the dyes have been found to be strongly affected by the mentioned parameters. These were obtained by the values of lmax at 206 and 620 nm at certain intervals of time. The results showed that zinc oxide was more active than titanium dioxide when the concentration of the catalyst was 1.6 g L-1. The rate of decolorization of industrial wastewater was found to be higher in basic medium. A radial mechanism for photocatalytic degradation with ultraviolet light and a photosensitilized degradation with visible light are proposed.